Kejahatan Penipuan Dengan Modus Undian Berhadiah Ditinjau Secara Kriminologis - Bakhtiar, Yusnanik (Universitas Malikussaleh, 2013)
The crime of fraud is one of the crimes against property. Fraud crimes is regulated in the PENAL CODE CHAPTER XXV, article 378 up to 395 in the call also with bedrog. Besides it is also regulated in ACT No. 22 of 1954 About Sweepstakes. There is some form of lottery such as drawing unconditionally, conditionally buy lottery, sweepstakes by issuing costs. There are many factors that cause a person committed a crime of fraud. Among them are the economic and environmental demands that cause someone desperate to do the fraud crimes. It can be seen from some of the existing theory of Criminology include the differential Association theory, anomie theory, and the theory of subculture. One way to avoid the crime of fraud is in a way always wary if there are sms or phone on behalf of lottery with prizes, check out the relevant parties if the prizes on behalf of relocation. There are some efforts to tackle this fraud crime preventive efforts and the efforts of both the repressive. Preventive effort is prevention efforts before the occurrence of the crime while efforts have been made in the repressive crime fraud through the coaching given to the perpetrators of the crime of fraud.